Verso una rinnovata mistagogia L’impostazione della mistagogia basata sulla tipologia biblica - Nikolaj Aracki Rosenfeld (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Biblical typology is the basis of any mystagogy because, through it, the Christian sees the entire plan of God unfolded, fulfilled in Christ, along with the persons, realities, and events that prophetically prefigured His coming. In various fields of theological reflection, the term „mystagogy”, so dear to the liturgical and spiritual tradition of Christian antiquity, has emerged with renewed vigour. In the great patristic mystagogies, the biblical passage takes center stage and shapes the very method of mystagogy: for the Fathers, mystagogy is nothing other than biblical typology applied to the liturgy. Therefore, in order to fully participate in the mysteries of Christ and his message, it is necessary to appropriate and adopt biblical typology. Only this enables us to move toward a renewed mystagogy.